El principio de in dubio pro- actione e imparcialidad del juzgador en el caso de recusación, en el margen del análisis jurisprudencial de la sentencia nro. 7-21-cp de la Corte Constitucional del Ecuador. - Ordónez Japón, Ítalo Aldahir (2023)
The present titling work prior to opting for the Lawyer Title, deals with: “THE PRINCIPLE OF IN DUBIO PRO- ACTIONE AND IMPARTIALITY OF THE JUDGE IN THE CASE OF DISCLAIM, WITHIN THE MARGIN OF THE JURISPRUDENTIAL ANALYSIS OF JUDGMENT NRO. 7-21-CP OF THE CONSTITUTIONAL COURT OF ECUADOR” The investigation allows us to know how the constitutional principles of speed and impartiality in the Ecuadorian legal system can be exercised and arbitrated for the benefit of the defendants. The recusal is a judicial process which allows the procedural subjects to request that a judge be removed from the hearing of their case, when their impartiality is affected, the same that is presented in the causes of their knowledge, due to the commitment they may have. judges with the procedural parties in the litigation, either because these judges have a direct or indirect interest of an affective, political, religious or personal nature, with the procedural subjects, experts or witnesses. The main purpose of this investigation is to determine if the rescission is a mechanism that guarantees impartiality, for this reason an analysis of SENTENCE NRO was carried out. 7-21- CP OF THE CONSTITUTIONAL COURT OF ECUADOR and the procedure carried out before the challenge was observed. It should be noted that the challenge procedure is created with the purpose that its application prevents and eliminates the lack of impartiality in the judges in the Ecuadorian procedural system, promoting the effective enjoyment of the rights to due process and effective judicial 4 protection; Prior to the recusal trial, the judge will have the obligation to excuse himself and separate himself from the knowledge of a case when his personal interests are benefited or harmed by ruling in favor of or against one of the procedural subjects. Partiality is constituted as the main cause for the presentation of an excuse or recusal as the case may be, however, partiality is also configured as an exhaustive prohibition of judges for the exercise and fulfillment of justice; the excuse will be ex officio by the Judge, due to the absence of the excuse, the procedural party that is affected may present the corresponding demand for recusal. The Ecuadorian procedural system presents the recusal as the solution to existing problems and controversies by the judges when they see themselves committed or inclined to favor one of the parties without strict compliance with the laws established for each procedure.